Analysis of Using Online Learning Media Via Whatsapp During The Covid-19 Pandemic At Smp Negeri 8 City of Bengkulu - Lensi Herlina; Monika Dwi Anggita; Sisi Mulia Utami; Ahmad Walid (STKIP Modern Ngawi, 2022)
The learning process during the COVID-19 pandemic must be carried out online. The use of media in learning becomes very important. This study aims to describe the effectiveness of using the WhatsApp application as a learning medium during the COVID-19 pandemic. The research subjects here are eighth grade students of SMP Negeri 8 Bengkulu City. This type of research is descriptive quantitative research. Data collection techniques in this study were carried out in the form of a questionnaire. The results obtained are that the use of WhatsApp as an online learning medium during the Covid-19 pandemic can be said to be quite effective with a score of 59.6% based on filling out a questionnaire by 15 class VIII students at SMP Negeri 8 Bengkulu City in achieving the goal. learning.